Electromagnetic navigation diagnostic bronchoscopy in peripheral lung lesions - Eberhardt, Ralf; Anantham, Devanand; Herth, Felix; Feller-Kopman, David; Ernst, Armin (Chest, 2007)
Electromagnetic navigation bronchoscopy (ENB) with biopsy under fluoroscopic guidance has enhanced the yield of flexible bronchoscopy in the diagnosis of peripheral lung lesions. However, the accuracy of ENB navigation suggests that the addition of fluoroscopy is redundant. Data were prospectively collected to determine the yield of ENB without fluoroscopy in the diagnosis of peripheral lung lesions. ENB was performed via flexible bronchoscopy (superDimension/Bronchus system; superDimension Inc; Plymouth, MN). Biopsy specimens were obtained through the extended working channel after navigation. Fluoroscopy was not utilized, but post-transbronchial biopsy chest radiographs were obtained to exclude pneumothorax. The primary end point was diagnostic yield, and the secondary end points were navigation accuracy, procedure duration, and safety. Analysis by lobar distribution was also performed to assess performance in different lobes of the lung. Ninety-two peripheral lung lesions were biopsied in the 89 subjects. The diagnostic yield of ENB was 67%, which was independent of lesion size. Total procedure time ranged from 16.3 to 45.0 min (mean [+/- SD] procedure time, 26.9 +/- 6.5 min). The mean navigation error was 9 +/- 6 mm (range, 1 to 31 mm). There were two incidences of pneumothorax for which no intervention was required. When analyzed by lobar distribution, there was a trend toward a higher ENB yield in diagnosing lesions in the right middle lobe (88%). ENB can be used as a stand-alone bronchoscopic technique without compromising diagnostic yield or increasing the risk of pneumothorax. This may result in sizable timesaving and avoids radiation exposure.